Seasonal phytoplanktonic diversity of padmala pond in ranthambhore fort, District Sawai Madhopur, Rajasthan, India - JYOTI RAJAWAT; VIJENDRA K. SHARMA (International Journal of Pharma and Bio Sciences, 2018)
The assessment of the quality of water involves the analysis of physicochemical, biological and microbiological parameters that reflect the biotic and abiotic status of an ecosystem. The water samples were collected for two years (2014 to 2016) from Padmala pond of Ranthambhore Fort located in the district of Sawai Madhopur (Rajasthan). The analyzed physicochemical parameters fluctuated according to seasons except D.O. The value of all parameters is higher in summer except the D.O. content. Total 17 algal genera and 30 species belonging to 4 classes have been accounted from the two sites of the pond. Few species were recorded throughout the year while others were found fluctuating in different seasons, mainly in summer and winter. During the summer season, the algal species that were recorded belong to Chlorophyceae (10 species) and Cyanophyceae (9 species) as the most dominant group. While Bacillariophyceae (2 species) were most dominant during winter. The most common algal species reported from the ponds were Microcystis aeruginosa, Anabaena azollae, Nostoc muscorum, Microcystis flos-aquae, Scenedesmus quadricauda and Spirogyra sp. throughout the investigation.